Ayurvedic Management of Shwitra (Vitiligo) - Raj Kumar Jangir; Jyoti Kumari Jangir (International Journal of Ayurveda and Pharma Research, 2024)
In Ayurveda, skin diseases are classified under Kushta Roga with Shwitra being one of its notable conditions. Shwitra is characterized by whitish patches on the skin, primarily resulting from the involvement of Sapta Dravyas i.e., Vata, Pitta, Kapha, Rasa, Rakta, Mamsa, and Meda. Shwitra is often correlated with vitiligo, a hypopigmentation disorder impacting about 1% of the global population. While Shwitra is not harmful in a physical sense, it can significantly affect a child’s social and mental well-being. Methodology- This case report presents a 13-year-old female patient came to SBLD Panchakarma OPD with complaint of white patches on her face and both upper and lower limbs, accompanied by mild itching but no burning sensation since one year. The initial treatment involved Shamana chikitsa followed by Shodhana Chikitsa for a period of three months, with regular follow-ups to assess changes in the size, no. and colour of the patches. This article discusses the Ayurvedic management of Shwitra, highlighting treatment efficacy. Result and Discussion- The patient exhibited notable improvement following Virechana and subsequent Shamana Aushadis. The treatment protocol effectively facilitated the re-pigmentation of the de-pigmented patches. No. of patches are reduced after treatment. This case underscores the potential of Ayurvedic treatments for Shwitra, reaffirming their efficacy as described in classical texts. Such outcomes could be fundamental in managing future cases of similar skin conditions. Conclusion- The rising incidence of vitiligo is linked to lifestyle factors, making it essential to address its causes through Ayurveda. Shwitra Chikitsa offers treatments that improve pigmentation and mental well-being. Using Shodhana and Shamana therapies, practitioners can target the root causes, reduce patches, and restore normal skin pigmentation while preventing recurrence.